Influence of soil-structure interaction on dynamics of offshore wind turbine structure - T. Wansuwan (2022)
Offshore wind turbines have a potential to provide a reliable alternative source of energy. The wind turbine structure must be designed by keeping the fundamental natural frequency of the system away from the excitation frequencies so as to avoid the resonance condition. This paper presents a finite element-based dynamic analysis of offshore wind turbines with monopile foundations including the soil-structure interaction effects to assess the natural frequencies of wind turbine systems. The model for wind turbine structure developed herein is based on the Euler-Bernoulli beam-column theory with a varying stiffness along its length. A tapered tubular wind turbine column is considered for analysis. Selected numerical results are presented to portray the influence of various foundation systems, i.e., fixed support, elastic end-support model with a set of springs and nonlinear p-y model, on natural frequency of offshore wind turbines. The numerical results for selected case studies suggest that the interaction between the foundation and wind turbine structure should be taken into consideration in the analysis for evaluating the natural frequency of offshore wind turbine systems.